2004
DOI: 10.1002/jsfa.1924
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive phenolic compounds of cowpeas (Vigna sinensis L). Modifications by fermentation with natural microflora and with Lactobacillus plantarum ATCC 14917

Abstract: In this work we have determined the phenolic composition of raw cowpeas (Vigna sinensis L) of the variety Carilla by HPLC/PAD/MS and have studied the effect of fermentation, both spontaneous and with Lactobacillus plantarum ATCC 14917, on the phenolic compounds. This variety contains mainly ferulic and p-coumaric acids esterified with aldaric acids, together with the cis and trans isomers of the corresponding free acids. Hydroxybenzoic acids such as gallic, vanillic, p-hydroxybenzoic and protocatechuic were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
130
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(159 citation statements)
references
References 38 publications
(31 reference statements)
20
130
0
Order By: Relevance
“…The trans-ferulic acid, 5-Ocaffeoylquinic acid, quercetin rutinoside and quercetin glucuronide (compounds 1, 5, 29, 30) were identified by comparison of their retention times and UV spectra with respective reference substances. The cis-ferulic acid (2) was identified in agreement with data from Dueñas et al [23].…”
Section: Resultssupporting
confidence: 90%
“…The trans-ferulic acid, 5-Ocaffeoylquinic acid, quercetin rutinoside and quercetin glucuronide (compounds 1, 5, 29, 30) were identified by comparison of their retention times and UV spectra with respective reference substances. The cis-ferulic acid (2) was identified in agreement with data from Dueñas et al [23].…”
Section: Resultssupporting
confidence: 90%
“…During fermentation, microorganisms break down cereal grain matrices leading to release of bound phytochemicals (Dordevic et al., 2010). L. plantarum and B. subtilis have been previously reported to possess β‐glucosidase that can cleave glucoside bonds between phytochemicals and sugars thereby releasing phytochemicals (Duenas, Fernandaz, Hernandez, Estrella, & Munoz, 2005; Kuo, Cheng, Wu, Huang, & Lee, 2006). Thus, the ability of fermentation to increase antioxidant properties of foods can be explored as a cost‐effective way to reduce oxidative stress within the body after consuming such foods.…”
Section: Effect Of Fermentation On Nutrients and Mineralsmentioning
confidence: 99%
“…In contrast, the TFC of the nonfermented control extract was decreased by approximately 3%. Dueñas et al (2005) reported that complex polyphenols could be biotransformed into other simpler and more biologically active compounds by microorganisms. In this study, it was presumed that L. plantarum also biochemically transformed the polyphenols into other components.…”
Section: Fermentationmentioning
confidence: 99%